Heat-insulating properties of rigid polyurethane foams synthesized with use of vegetable oils - based polyols - Prociak, A. (Polimery, 2022)
The vegetable oil (rapeseed, soybean, sunflower or linseed one) - based polyols prepared on a laboratory scale (Table 1) were used to modify the compositions of petrochemical polyurethane systems (Table 2). Rigid polyurethane foams based on them were prepared in two molds differing in the direction of free foaming of reaction mixture. Apparent density of the foams and thermal conductivity (l) values were determined as well as the analyses of the cell structures (Table 3 and 4, Fig. 1 and 2). Factor ? was measured at average temperatures in the range 0-50°C (Fig. 3). It has been found that modification of petrochemical polyurethane system with hydroxyl derivatives of vegetable oils in amounts up to 30% let obtain the foams showing better heat-insulating properties in the investigated temperature range.